A comparative study of the outcomes of fixation of fractures of distal femur by femoralnailing vs distal femoral locking compression plate (Panacea Journal of Medical Sciences, 2022)
Introduction: Distal femoral fractures are much less common than hip fractures and account for 7 % of all femoral fractures.Aims To determine the fracture characteristics (AO type, Muller’s classification). To study the advantages of fixation with distal femoral locking compression plates and retrograde intramedullary supracondylar nailing.Materials and Methods: The present comparative study was conducted between May 2019 to November 2020 in department of othropeadics. Sample size of 30 patients presenting with supracondylar fractures of the femur were treated by distal femoral locking compression plates, dynamic condylar screws and retrograde supra condylar nailing.Results: Out of 30 cases those treated by supracondylar nail had an average healing time of 14.8 weeks and those treated by locking compression plate had an average healing time of 15.9. Among the 30 cases of supracondylar fracture fixed by supracondylar nail 14 were scored as good and one was scored as excellent, whereas those fixed by locking compression plate 14 were scored as good and 1 cases was scored as fair. Out of 30 cases of supracondylar fracture fixed none had any intraoperative complications barring one which had break of drill bit intraoperatively and stayed insitu to the bone, there were no intances of surgical wound infections. The intraoperative blood loss was significantly lower when the fractures were fixed by supracondylar nail which averaged to 150ml when compared to the fixations by locking compression plate which averages to 300ml.Conclusion: The supracondylar nail is more ideal when compared to the distal femoral locking compression plate as there is less operation time, less blood loss, more range of movement, less soft tissue stripping & faster radiological union when compared to the distal femoral locking compression plate. Fracture personality & soft tissue quality.